100 things every designer needs to know about people - Weinschenk, Susan (Berkeley, CA : New Riders, 2011)
Provides information and examples to help designers create products, applications, Web sites, and print materials that match the way people think and feel.
How people see -- How people read -- How people remember -- How people think -- How people focus their attention -- What motivates people -- People are social animals -- How people feel -- People make mistakes -- How people decide.
Includes bibliographical references (p. 225-234) and index.
Keywords: Design -- Psychological aspects